Public Value Creation sebagai Penggerak Transformasi Pelayanan Publik Kontemporer - Sri Yulianty Mozin; Romy Tantu; Rahmatia Pakaya; Alexander H. Badjuka (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The transformation of public services has become a key priority in public administration reform, driven by growing public demands for government services that are more responsive, transparent, and oriented toward the public interest. In this context, the concept of Public Value Creation has emerged as an approach that emphasizes the creation of social value as the primary objective of public service delivery. This study aims to analyze the role of Public Value Creation as a conceptual framework in public service transformation oriented toward the public interest. The study employs a qualitative approach through a literature review, examining various relevant academic sources on public value theory, contemporary public administration, and public service transformation. The findings indicate that Public Value Creation plays a role in driving a paradigm shift in public service from an administrative bureaucratic orientation toward service focused on creating social benefits for the community. This approach also strengthens a community-centered service orientation, fosters collaboration between the government and various stakeholders, and supports public service innovation, including through the utilization of digital technology. The implications of this research suggest that the concept of public value can serve as a conceptual foundation for the government in designing more inclusive public service policies and innovations